Smart City Security Issues: Depicting Information Security Issues in the Role of an Urban Environment - Ferraz, Felipe Silva; Guimaraes Ferraz, Carlos Andre (Proceedings of the 2014 IEEE/ACM 7th International Conference on Utility and Cloud Computing, 2014)
For the first time in the history of humanity, more them half of the population is now living in big cities. This scenario has raised concerns related systems that provide basic services to citizens. Even more, those systems has now the responsibility to empower the citizen with information and values that may aid people on daily decisions, such as related to education, transport, healthy and others. This environment creates a set of services that, interconnected, can develop a brand new range of solutions that refers to a term often called System of Systems. In this matter, focusing in a smart city, new challenges related to information security raises, those concerns may go beyond the concept of privacy issues exploring situations where the entire environment could be affected by issues different them only break the confidentiality of a data. This paper intends to discuss and propose 9 security issues that can be part of a smart city environment, and that explores more them just citizens privacy violations.